2013
DOI: 10.2478/v10222-012-0093-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hot Smoking and Sun Drying processes on Nutritional Composition of Giant Tiger Shrimp (Penaeus monodon, Fabricius, 1798)

Abstract: There are information gaps in the knowledge of the impacts of traditional techniques of fish preservation used to meet market demands even though there are growing concerns of the effects of these methods of preservation on product forms and qualities. In this study the effects of commonly used preservation techniques of hot smoking and sun-drying on the nutritional composition of Penaeus monodon were investigated. Proximate values varied significantly (P<0.05) except for protein the dominant constituent with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
37
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 26 publications
7
37
2
1
Order By: Relevance
“…The observation could be due to reduction in their moisture contents as a result of the drying and smoking processes, which have been noted to result in increase of the dry matters, including protein composing of amino acids. The result of this study was supportive of the finding of Akintola et al [21].…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The observation could be due to reduction in their moisture contents as a result of the drying and smoking processes, which have been noted to result in increase of the dry matters, including protein composing of amino acids. The result of this study was supportive of the finding of Akintola et al [21].…”
Section: Resultssupporting
confidence: 92%
“…Yeast and moulds was highest (3.62 log count/g) for the unproccessed sample while the lowest (2.65) was obtained for the hot smoked sample. According to the report of Akintola et al [21], the reduced counts of Pseudomonas and coliforms recorded in the processed samples in the present study, may be attributed to reduced water activity and antimicrobial properties of phenolic compounds known to be associated with drying and smoking respectively. Values are means of three replicated samples; Means with different superscripts across columns are significantly different (P < 0.05).…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…However, foods are nowadays smoked for sensory quality rather than for the preservative effect. Yanar et al (2006) reported that the acceptance of smoked fish in developed countries is based primarily on the sensory characteristics it imparts to the product while Akintola et al (2013) confirmed the nutritional qualities and adequacies. In addition to this, smoking enhances preservation due to the dehydrating bactericidal and antioxidant properties of smoke such as phenol derivates, carbonyls, furan derivates, organic acids and their esters (Simko, 2002).…”
Section: Introductionmentioning
confidence: 96%
“…sundried and smoke dried indicated less moisture content than that of sundried, however, these findings are in line with that of Ande et al, (2012) who concluded that there is a great loss of water during the smoking process. According to Shehu et al, (2013), during smoking and sun drying processes, approximately one-quarters and one thirds of moisture is lost, which means that both processes are responsible for the lower moisture values indicated in this study. Furthermore, the study shows a huge variation in dry matter between dried fish samples and the fresh fish, this generally is the material that remains after the removal of water according to Figure 4. …”
Section: Proximate Chemical Compositionmentioning
confidence: 68%